Short term outcomes of robotic surgery after neoadjuvant treatment for locally advanced NSCLC: a comparison with the open approach - Gallina, Filippo Tommaso; Tajè, Riccardo; Forcella, Daniele; Alessandrini, Gabriele; Vizza, Francesco; Bovini, Rachele; Visca, Paolo; Sperduti, Isabella; Cappuzzo, Federico (Frontiers in Oncology, 2025)
IntroductionDespite thoracotomy remaining the gold standard in the treatment of locally advanced NSCLC after induction treatment, robotic surgery may improve perioperative outcomes. The object of this study is to compare robotic surgery with thoracotomy for the treatment of NSCLC after neoadjuvant treatment, analyzing primary the postoperative complications and secondary the length of hospital stay, the daily drainage volume and the neutrophils-to-lymphocyte ratio.MethodsThe study was designed as a single center and retrospective analysis. Patients with locally advanced NSCLC underwent neoadjuvant treatment followed by surgery between 01/2017 and 12/2023 were evaluated.ResultsA total of 60 patients were collected. The most frequent clinical stage was IIIa (38,3%). Platinum based chemotherapy was delivered in 56 patients; it was associated with immunotherapy in 28 cases and to radiotherapy in 14 cases. All the patients underwent lobectomy and systematic lymphadenectomy, 25 via robotic surgery. There was no significant demographic difference between the two cohorts except for preoperative radiotherapy; over one-third of patients in the open cohort received radiotherapy, while no patients in the robotic cohort did (p<0.001). The hospital stay was statistically significantly shorter in the robotic group (6 days (4-17) vs 8 (5 - 29); p=0.02). Postoperative complication rates were lower (42,8% vs 20%, p=0.04) and the daily drainage output was significantly lower (p=0.0001). The NLR evaluated in V postoperative days was significantly lower in the robotic group (3.36 ± 1.99 vs 7.27 ± 2.59, p=0.0001).ConclusionDespite significant selection bias between cohorts, particularly regarding the use of preoperative radiotherapy which might have influenced the outcomes, robotic surgery appears feasible and yields comparable short-term outcomes for patients with locally advanced NSCLC following neoadjuvant therapy.